OPINI AUDIT GOING CONCERN DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA - Rakatenda, Gusti Ngurah; Putra, I Wayan (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
The purpose of this study was to examine the effect of leverage, profitability, company size, tenure of audit and auditor reputation on a going concern audit opinion. This research was conducted at the manufacturing companies listed in Indonesia Stock Exchange period 2011-2014. Samples were obtained by 76 companies with non-probability sampling methods, particularly purposive sampling. Data analysis technique used is the logistic regression analysis. The analysis finds that leverage does not affect the going concern audit opinion. Profitability does not affect the going concern audit opinion. Audit tenure does not affect the going concern audit opinion. Reputation auditor does not affect the going concern audit opinion. In contrast to the size of the company that affect the going concern audit opinion.
Keywords: Going Concern Audit Opinion, Leverage, Profitability, Company Size, Audit Tenure, Auditor Reputation